Filmu ieskaņošanas pamatprincipi - Savenkova, Anna (Latvijas Universitāte, 2007)
Šajā darbā tiek aplūkotas dažādas tulkojuma metodes, kuras ir izmantotas, tulkojot filmas. Autore koncentrējas uz kultūras sniegšanas aspektiem, kā arī uz audiovizuālā konteksta svarīgumu tulkošanā no vienas valodas uz citu. Kursa darba mērķis ir, izskatot teorētisko materiālu par kultūru, filmu teoriju un filmu tulkošanas metodēm, izvēlēties vispiemērotākās pieejas sekmīgai filmu tulkšanai un ilustrēt tos ar analizētu piemēru. Izmantojot sakrāto teorētisko materiālu un analīzes rezultātus, darba rakstīšanas procesā tiek atklāts, ka audiovizuālo tekstu tulkošana ir speciāls, atšķirīgs no citiem, tulkojuma veids, un ka sekmīgai tulkošanai ir nepieciešama dziļa tēlu, vizuāla konteksta un to funkciju saprašana.

The given paper deals with the problems of film translation in general, and particularly with voicing-over. It provides an overview of the methods, approaches and theoretical terms used in translation in general, as well as on the three types of audiovisual translation. The present theme was chosen by the author for the reason that audiovisual texts comprise an important part of cross-cultural communication that is vital in today’s multicultural world. Moreover, the given theme has not been much investigated and provides a rich field for the further research. The goal of the paper is to investigate the challenges and difficulties the film translators face, to find out how the various strategies of translation influence the audience’s perception, understanding and interpretation of audiovisual texts and select the strategies suitable for film translation by means of a comparative analysis of a successful voicing-over translation and a translation of the same film script without its audiovisual context. In her study the author has compiled, investigated and analyzed various theoretical sources, and provided a brief analysis of the original script as well as a comparative analysis of translated materials.
Guide Lines to Voicing-Over
Keywords: Filoloģija